“Factores internos en el proceso educativo” - Lema Arequipa, Ana Gabriela (2022)
At present, education faces great challenges that, despite having a biological and psychological origin, influence educational processes: nutrition, personal hygiene and behavior, which have been called internal factors and are considered to be directly associated with the success or failure of the educational process. Indeed, ignorance of the internal factors in the educational process of children generates academic and social problems. In other words, learning problems can originate in phenomena that develop in the family and in society. In this sense, the objective of this project is to reflect on the incidence of internal factors in the educational process through a life history in order to strengthen it in the seventh year of general basic education of the Rafael Cajiao Enriquez Educational Unit. The methodology used was qualitative, since through an in-depth interview a life history was constructed in which the influence of internal factors in the educational process of a child in the seventh year of general basic education was described and interpreted. This made it possible to reflect on the importance of internal factors for an adequate learning process. As a result, a life history was obtained which made it possible to know how internal factors influence the educational process, showing that the educational process is a joint responsibility of the institution, the teacher, the student, the family and society. The disclosure of the results of the analysis of the proposed life history will allow educators and future educators of the country to know the incidence of nutrition, hygiene and behavior in the correct development of the students in the educational process.